Sifat Mekanik Komposit Serat Eceng Gondok dengan Filler Cu-Zn dan MgO untuk Kampas Rem Sepeda Motor - Oxa Rachmada; Sri Hastuti; R. Faiz Listyanda (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Brake linings are an important component in the vehicle braking system, but the use of hazardous materials such as asbestos causes environmental pollution. This research aims to analyze the effect of water hyacinth fiber content in composites with Cu-Zn and MgO fillers on brake lining wear and hardness, as a more environmentally friendly alternative. The experimental method was used with variations in the composition of water hyacinth fiber: brass powder: magnesium oxide powder: epoxy resin of 10%:40%:20%:30%, 15%:40%:20%:25%, 20%:40%: 20%:20%, and 25%:40%:20%:15%. The manufacturing process involves a compaction pressure of 2 tons for 10 minutes and sintering at a temperature of 200°C for 30 minutes. Vickers hardness testing refers to the ASTM E384 standard and wear testing refers to the ASTM G99-95a standard. The results showed that the highest hardness was obtained with a composition of 10% water hyacinth fiber (245.26 Kgf/mm2), with a composition of 15% water hyacinth fiber (240.88 Kgf/mm2), with a composition of 20% water hyacinth fiber (215.84 Kgf /mm2), and a water hyacinth fiber composition of 25% (194.48 Kgf/mm2). The lowest wear test results were at a composition of 10% water hyacinth fiber (0.00212 mm²/kg), at a composition of 15% water hyacinth fiber (0.00242 mm²/kg), at a composition of 20% water hyacinth fiber (0.00295 mm²/kg), and with a composition of 25% water hyacinth fiber (0.0031 mm²/kg). This shows that increasing the percentage of water hyacinth fiber can reduce the hardness value and increase brake lining wear.